Every man as a phenomenon of “forty and four”. Review of interpretation - Saja, Krystian (In Gremium. Studies in History, Culture and Politics, 2020)
The article aims to review the concept of reading the words "forty and four" from the drama of Dziady, part III of Adam Mickiewicz and presenting a new author’s interpretation. This interpretation will refer to the history of the Napoleon Bonaparte family. We will follow the links of Widzenie ks. Piotra with Napoleon I, Napoleon II and Ludwik Napoleon Bonaparte. Mickiewicz’s unwavering faith in the strength of this French line will also be analyzed.